An Analysis on Data Mining Processes on Big Data Framework - Sharmila Begam, M; Vetrivelan, N (International Journal of Computer Sciences and Engineering, 2014)
Apache HADOOP is a major novelty in the IT market household last decade. From modest early stages Apache HADOOP has develop a world-wide receipt in figures centers. It brings like dispensation in pointers of regular programmer. As additional figures middles ropes HADOOP platform, it develops authoritative to travel present figures removal procedures onto HADOOP stage for augmented like dispensation efficiency. By the outline of big figures analytics, This trend of transfer of the present figures removal procedures to HADOOP stage has develop rampant. In this review paper, we discover the present transfer doings and tests in migration. This newspaper will leader the booklovers to suggest answers for the present tests in the migration.